Dynamics and asymmetric rent adjustments in the office market in Warsaw - Nowak, Krzysztof; Gluszak, Michal; Belniak, Stanislaw (International Journal of Strategic Property Management, 2020)
Dynamics of rent, vacancy, supply and demand on the office market of emerging commercial real estate markets have long been under-researched. The paper fills the gap in economic literature by investigating the growing office market in Warsaw. In particular, we evaluate whether the influence of demand and supply shocks differ depending on the current market conditions. Using Error Correction Model approach, we investigated the rent adjustments on the office market in Warsaw, which is the major property market in Central and Eastern Europe. We replaced variables of the basic model with asymmetric variables to check for asymmetric adjustments in the office market. The study period covers data from 2005:1Q to 2016:1Q. The empirical results suggest that demand shock had a stronger impact on rent when the market vacancy rate was below the average for the period considered. Additionally, the demand shock had a stronger impact on rent when the rent was above the equilibrium level.